Anti-cancer Activity of Strobilanthes crispus Against Colon Cancer Cell Lines: A Scoping Review of Literature - Muhammad Arif Hakimi Salihuddin; Abdul Aziz Azlan; Siti Aisyah Abd Ghafar; Haslinda Ramli; Rohazila Mohamad Hanafiah (Universiti Putra Malaysia, 2026)
Indexed by Scopus/MyCite